Experimental Study on Dynamic Characteristics of Shut-In and Restart Process in Water Drive Strong Heterogeneous Oil Reservoir. (14th April 2021) - Chen, Hao; Yang, Mingyang; Yu, Haizeng; Yang, Shenglai; Wang, Mibang
Abstract : The main purpose of this investigation is to study the dynamic characteristics of shut-in and restart process in reservoirs with high water cut and strong vertical heterogeneity. The physical model, which includes three layers with low, medium, and high-permeability from top to bottom, was made according to the similarity law. Water drive test, the first restart test, and the second restart test were conducted, respectively. Water cut, oil recovery, and saturation distribution of the remaining oil were obtained during the tests. On this basis, mechanisms of shut-in and restart process of the reservoir were analyzed. It is concluded that appropriate developing plan such as layering mining and cyclic waterflooding should be implemented for developing strong heterogeneity reservoirs. The shut-in and restart tests showed that closing the water-flooded layer is beneficial for enlarging the sweep volume. Besides, water cut of 98% does not mean the economic limits of waterflooding. Under the effect of capillary force and gravitational differentiation, oil and water will redistribute in the formation. The redistribution of the oil and water, the fluctuation of the pressure difference, and the rebuild of the flow path, which produce parts of the bypassed oil, are the main mechanisms of the recovery enhancement by shut-in and restart operation. It should be noted that the shut-in and restart process indeed prolongs the waterflooding development. However, simply replying on the oil and water distribution under static conditions cannot greatly enhance the oil recovery.